Identification of a homozygous nonsense variant of LYST gene: a case report of Chediak-Higashi syndrome - Kumar, Sudesh; Anushree, Akansha; Niranjan, Tripathi Siddharth (International Journal of Contemporary Pediatrics, 2025)
Chediak-Higashi syndrome is a rare autosomal recessive disease manifested as hypopigmentation of skin hair, recurrent infection, abnormal organelles in circulating granulated cells, and neurological dysfunction. We describe a case of an 8-year-old female child diagnosed with Chediak-Higashi syndrome on the basis of the manifestation of recurrent chest infection with diarrhoea with multiple hypopigmentation patches and silvery hair, with a sibling of similar presentation without splenomegaly, which was further confirmed by genetic study as a homozygous nonsense mutation of the LYST gene. The child was treated with antimicrobials and a high dose of vitamin C and referred to a higher center for HSCT (hematopoietic stem cell transplantation). Chediak-Higashi scan be easily diagnosed before the accelerated phase by demonstrating large intra-cytoplasmic granules and cure by promoting bone marrow transplantation.